NETWORK CHANGE AND DEVELOPMENT OF BUMIPUTERA ENTREPRENEURS: THE STUDY OF MULTIPLE-CASES OF SMALL BUSINESSES IN THE SOUTHERN REGION OF MALAYSIA - Omar, Siti Sarah; Higgs, Malcolm (Journal of Technology Management and Business, 2015)
This paper seeks to empirically explore the dynamics of change and development of network ties of Bumiputera entrepreneurs during the firms’ tipping points. Literature review shows that many studies have explored the mix of strong and weak ties in small businesses linking them to stages of business development. More recent literature, however, has conceptualised firm growth through the notion of critical problems or ‘tipping points’ that must be successfully tackled in order to continue on a development path. While the importance of network ties has been well documented in relation to growth stages, limited work has investigated the contribution that strong and weak ties make as a firm faces specific tipping points, thus showing a call for further investigation. This is a qualitative study involving eight cases of small-sized food manufacturing firms in the Southern region of Malaysia. The main data collection method is an in-depth interview with the owner-managers using Critical Incident Interview Technique.  The triangulation of data has been carried out by interviewing individuals who are seen as strong and weak ties of the network. This study explores 10 themes of tipping points that trigger network change and development; these are financial problem, new market entry, strategic orientation, people management, competition, external events and/or environmental factor, trust breaking, network broker, multidimensionality of entrepreneurial-level context and multidimensionality of dyadic-level context. This study adds value to the network change literature and provide managerial and policy implications.